Efektivitas Pembelajaran Berbicara Bahasa Inggris Melalui Media Sosial Youtube Pada Kanal English Singsing - Nasution, Ervina; Nurchaerani, Meiyanti (Rumah Riset Publisher, 2024)
The purpose of this study is to determine the efficacy of using YouTube video material to teach speaking. YouTube video material denotes material created by researchers in the form of videos sourced from the YouTube application. The designed material is vocabulary and conversation. The purpose of this research is to examine students' speaking skills in terms of vocabulary and pronunciation, as well as conversation, using YouTube video material. This is an observational research method. The participants in the study were 40 eighth-grade students from SMPN 69 West Jakarta. The researcher's research material consists of two different YouTube channels on the same topic. Students took part in an eight-week trial from March 1, 2022 to April 27, 2022. Students' perspectives were used to collect data for the research instrument. The test was also completed by recalling vocabulary and practicing conversations with other students. The differences in the speaking comprehension scores of students' work show that YouTube has an impact on student performance. This positive outcome implies that students at SMPN 69 West Jakarta can benefit from using YouTube videos to communicate. It is also regarded as a motivator for students to improve their speaking comprehension skills and gain a deeper understanding of English.